2001
DOI: 10.1580/1080-6032(2001)012[0002:anparc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide and red cell 2,3-diphosphoglycerate in patients with chronic mountain sickness

Abstract: These findings suggest that overproduction of ANP and 2,3-DPG at high altitudes may play an important role in the pathophysiology of chronic mountain sickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous studies in Han Chinese and Tibetans have reported high levels of BNP, vascular endothelial growth factor, and endothelin-1 in individuals with CMS compared with healthy highlanders [43,44]. We measured pro-BNP levels in HAs and those with CMS, but obtained different results.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies in Han Chinese and Tibetans have reported high levels of BNP, vascular endothelial growth factor, and endothelin-1 in individuals with CMS compared with healthy highlanders [43,44]. We measured pro-BNP levels in HAs and those with CMS, but obtained different results.…”
Section: Discussionmentioning
confidence: 92%
“…In clinical studies, a significant negative correlation between pulmonary oxygen tension, plasma ANP level, pulmonary artery pressure and pulmonary vascular resistance has been observed in normal subjects and patients with heart and lung disease (Adnot et al, 1989;Chen, 2005;Ge et al, 2001;Klinger and Cutaia, 1996). ANP binds to type A natriuretic Life Sciences 79 (2006) 1357 -1365 www.elsevier.com/locate/lifescie peptide receptors (NPR-A) in the pulmonary circulation, relaxing preconstricted pulmonary arteries and inducing pulmonary vasodilation in rat, dog or human exposed to hypoxia (Foster et al, 1997;Hohne et al, 2003;Jin et al, 1990Jin et al, , 1991Rogers et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…This is an important observation as it is well known that the incidence of chronic mountain sickness increases with age, and the disease is associated with overproduction of ANP. 12,31,32 The hemoglobin value of Ͻ21.3 32 in HANs of this study rules out excessive erythrocytosis.…”
Section: Discussionmentioning
confidence: 68%